2006
DOI: 10.1634/stemcells.2004-0150
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Proliferation of Human Embryonic Stem Cell–Derived Neuroepithelial Cells Using Defined Adherent Culture Conditions

Abstract: To proliferate and culture these derived NEP cells, ideal conditions were obtained using neurobasal medium supplemented with B27 and basic fibroblast growth factor in 5% oxygen. NEP cells were continuously propagated for longer than 6 months without losing their multipotent cell characteristics and maintained a stable chromosome number. STEM CELLS 2006;24:125-138

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
197
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 42 publications
10
197
1
1
Order By: Relevance
“…Some in vitro studies have suggested that stem cells lose expression of stem cell markers as they differentiate. 42,43 In our study, we observed that some markers were expressed focally in tumor sections, but there was no co-expression of markers in the same group of cells. This finding may suggest a sequential loss of marker expression during the maturation process, or that within the same tumor there might be different clones of progenitor cells in different stages of maturation depending on how far through the differentiation process the progenitor had proceeded before the process was interrupted.…”
Section: Discussionmentioning
confidence: 44%
“…Some in vitro studies have suggested that stem cells lose expression of stem cell markers as they differentiate. 42,43 In our study, we observed that some markers were expressed focally in tumor sections, but there was no co-expression of markers in the same group of cells. This finding may suggest a sequential loss of marker expression during the maturation process, or that within the same tumor there might be different clones of progenitor cells in different stages of maturation depending on how far through the differentiation process the progenitor had proceeded before the process was interrupted.…”
Section: Discussionmentioning
confidence: 44%
“…NPs were derived from WA09 hESC and cryopreserved as described previously [2]. They were subcultured on polyornithine-and laminincoated dishes using neurobasal medium (Gibco, Grand Island, NY, http://www.invitrogen.com) supplemented with 2 mM L-glutamine (Gibco), 1Â penicillin/ streptomycin (Gibco), 1Â B27 (Gibco), 20 ng/ml of FGF2 (Sigma-Aldrich, St Louis, MO, http://www.sigma aldrich.com), and 10 ng/ml LIF (Chemicon-Millipore, Billerica, MA, http://www.millipore.com/).…”
Section: Np Propagation and Derivation Of Neuronsmentioning
confidence: 99%
“…We have previously derived a self-renewing but fate-restricted neural progenitor (NP) cell line from hESC that can generate highly enriched neuronal populations under specific conditions [2,3], thus serving as a potentially unlimited source of human neurons for both basic [4] and applied research [5]. This progenitor line has previously been used to study neurotoxicity, differentiation to specific neuronal phenotypes, drug screening, and transplantation experiments in rodent models of stroke [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods to obtain neural differentiation have been reported. These include embryoid body formation and selection in NSC medium [5][6][7], sorting with CD133 after differentiation [8], selecting neurosphere forming cells after plating cells in low density [9], a direct differentiation of adherent culture in defined medium [10,11], or enhancing/biasing neural differentiation by altering bone morphogenic protein/transforming growth factor-␤ signaling or altering Notch signaling [12][13][14]. In all of these processes, a number of nestin-positive dividing populations can be obtained that express neural markers, and these populations can be induced to differentiate into neurons, astrocytes, and immature oligodendrocytes.…”
Section: Introductionmentioning
confidence: 99%